Refleksi Teologis Praksis Pelayanan Katekese Kaum Religius Bagi Umat Kristiani dan Tantangannya - Marianus Elki Semit; Jevannia Piter Dori Mudaj; Yohanes Geradus Ulung Fokang; Yohanes Wilson Bei Meo (Lumen: Jurnal Pendidikan Agama Katekese dan Pastoral, 2024)
This writing focuses on catechesis services, which are an integral part of ecclesiastical life for Christian believers. It is important for deepening the understanding of faith truths and their implementation in daily life within the social community. In this context, it aims to explore the relationship between theological understanding and practice in catechesis services for religious communities within the Christian context. Through a reflective theological approach, the author discusses how catechesis services can serve as a means to strengthen the foundation of believers' faith, integrate the teachings of Jesus Christ with the concrete experiences of Christian believers, and facilitate spiritual growth. The everyday reality is that in the struggle of life as a Christian, many still do not know Jesus Christ, as seen in our tendency to harbor mutual hatred towards one another. The methodology employed in this academic work includes literature review and practical findings from participating in a community service program at SMAK Bakti Luhur. The findings suggest that as followers of Jesus Christ, we must always acknowledge Him as the Savior of humanity, the only begotten Son of God the Father, and we, as believers, represent His presence in the world